Pediatric clinical pharmacology - Seyberth, Hannsjörg W.; Rane, Anders; Schwab, M. (Matthias) (Handbook of Experimental Pharmacology, 2011)
The objective of this volume is to give an overview of the present state of the art of pediatric clinical pharmacology including developmental physiology, pediatric-specific pathology, special tools and methods for development of drugs for children (assessment of efficacy, toxicity, long-term safety etc.) as well as regulatory and ethical knowledge and skills. In the future, structural and educational changes have to lead back to a closer cooperation and interaction of pediatrics with (clinical) pharmacology and pharmacy.